Genomic divergence and lack of introgressive hybridization between two 13‐year periodical cicadas support life cycle switching in the face of climate change. Issue 21 (14th October 2016) - Koyama, Takuya; Ito, Hiromu; Fujisawa, Tomochika; Ikeda, Hiroshi; Kakishima, Satoshi; Cooley, John R.; Simon, Chris; Yoshimura, Jin; Sota, Teiji
Abstract: Life history evolution spurred by post‐Pleistocene climatic change is hypothesized to be responsible for the present diversity in periodical cicadas ( Magicicada ), but the mechanism of life cycle change has been controversial. To understand the divergence process of 13‐year and 17‐year cicada life cycles, we studied genetic relationships between two synchronously emerging, parapatric 13‐year periodical cicada species in the Decim group, Magicicada tredecim and M. neotredecim . The latter was hypothesized to be of hybrid origin or to have switched from a 17‐year cycle via developmental plasticity. Phylogenetic analysis using restriction‐site‐associated DNA sequences for all Decim species and broods revealed that the 13‐year M. tredecim lineage is genomically distinct from 17‐year Magicicada septendecim but that 13‐year M. neotredecim is not. We detected no significant introgression between M. tredecim and M. neotredecim / M. septendecim thus refuting the hypothesis that M. neotredecim are products of hybridization between M. tredecim and M. septendecim . Further, we found that introgressive hybridization is very rare or absent in the contact zone between the two 13‐year species evidenced by segregation patterns in single nucleotide polymorphisms, mitochondrial lineage identity and head width and abdominal sternite colour phenotypes. Our study demonstrates that the two 13‐year Decim species are of independent origin and nearly completely reproductively isolated. Combining our data with increasing observations of occasional life cycle change in part of a cohort (e.g. 4‐year acceleration of emergence in 17‐year species), we suggest a pivotal role for developmental plasticity in Magicicada life cycle evolution.